Endoscopic treatment of congenital Vallecular cysts: single centre experience - Naserrudin, Nadia Syafeera; Abu Bakar, Saraiza; Zakaria, Atiqah Farah (Japan International Cultural Exchange Foundation, 2019)
Objective: This case series aim to describe the incidence of congenital vallecular cyst, review their clinical presentation, laryngoscopy findings, concurrent other laryngeal diseases and its surgical management. Design: Retrospective case series. Materials and methods: We present a series of 7 patients with congenital vallecular cyst over 27 months's duration between 2016 to first quarter of 2018 in our centre. Results: All of the 7 patients have stridor as their clinical presentation. 14.3% presents as an acute upper airway compromise requring immediate endotracheal intubation. 57% has associated laryngomalacia. All patients had at least a direct laryngoscopy and marsupialization. Vallecular cyst was first noted under general anaesthesia during direct laryngoscoy in 29%. Conclusion: Controlled direct laryngoscopy under general anaesthesia should be mandatory in all congenital stridor as vallecular cyst may be missed during bedside laryngoscopy. It is vital for early recognition of congenital vallecular cyst due to its potential life threatening complication from a compromised airway.